Potensi Energi Arus dan Tinggi Gelombang Laut Indonesia Berdasarkan Data Penginderaan Jauh - Alamsah, Azwar; Wahjudi, Ari; Moon, Park Jae; Hamidi, Nurkholis; Widhiyanuriyawan, Denny (TECHNO-SOCIO EKONOMIKA, 2025)
Indonesia's energy demand continues to increase, with a primary reliance on fossil fuels that contribute to environmental issues, such as rising CO₂ emissions. To address this challenge, this study explores the potential of renewable energy from wave and ocean current sources. The research process analyzes the energy potential generated from waves and ocean currents across Indonesian waters using the WAVEWATCH-III method to model ocean data over a 10-year period, focusing on energy potential at strategic locations in Indonesian waters. The results show that the energy potential from ocean currents ranges between 120–150 kW, with strategic locations around straits, such as the Makassar Strait and the Java Sea. Meanwhile, the wave energy potential reaches approximately 2.5 GW over a three-month period, thanks to Indonesia’s extensive coastline of 99,093 km. Spatial and temporal analyses reveal significant variations in Sea Level Anomaly (SLA) values, which can be utilized for the development of renewable energy projects. The conclusion of this study emphasizes the need for a deeper understanding of ocean current and wave dynamics to maximize the utilization of renewable energy potential in Indonesia. Spatial and temporal analyses show significant variations in SLA values across Indonesia, reflecting the dynamics of ocean currents. Understanding these changes is crucial for planning adaptive ocean current energy projects, and seasonal trend analysis can help optimize the use of ocean current patterns.